The effect of the (4E x 2) model on the literary achievement of fifth-grade female students in Rhetoric and application material (Journal of the College of Basic Education, 2022)
The current research aims to identify the effect of the (4E x 2) model on the literary achievement of fifth-grade female students in the subject of rhetoric and application. The research sample consisted of (40) female students from the fifth literary class in AL- Rabab Prep of the Baghdad Education Directorate Al-Karkh Third, for the academic year (2020-2021), chosen randomly to apply the experiment, where Division (B) represented the experimental group by (20) students, and the Division (C) The control group was represented by (20) female student The two researchers rewarded the two research groups (experimental and control) in the following variables: (the chronological age of the students calculated in months, the academic achievement of the fathers, the academic achievement of the mothers The grades of the Arabic language subject for the previous academic year and the test of language ability,) The two researchers prepared the research tool (the achievement test), as it consisted in its final form of (20) paragraphs (eighteen objective paragraphs and two essay paragraphs), and its validity and reliability were verified.After the end of the experiment, which lasted over a period of (11) week, the researchers applied the achievement test, and by using the statistical bag (SPSS-28), the results of the current research showed (the students of the experimental group who study the rhetoric subject, according to the model (4E x 2), outperformed the control group students. The following will study the same subject in the usual way in the achievement test .